Common Causes of Vaginal Infections in Women with Vaginal Discharge Attending the Outpatient Clinics of the Maternity Teaching Hospital in Erbil - Saeed, Zahida Haris; Mohammad, Nisreen Jasim; Ismail, Runak Ali; Shekh Mohammad, Samira Salim (Diyala Journal of Medicine, 2019)
Background: Vaginal infections are common gynecological problem of women attending consultancy clinics. Objective: To find out the most common causes of vaginal infections among women in Erbil city. Patients and Methods: A cross sectional study carried out at the Consultancy Clinics of Erbil Maternity Teaching Hospital through the period from 1st of July 2015 to 31st of January 2016 on a convenience sample of 101 women in reproductive age attending the clinics suffering from vaginal discharge. Vaginal specimen was taken from each woman by sterile cotton with assistance of nurse, and was sent for culture and sensitivity test in the hospital laboratory. Results: Culture results showed growth of normal flora in 29.7% of women, bacterial growth in 29.7% of women, fungal growth (Candida albicans) in 22.8% of women and mixed growth (bacterial and fungal) in 17.8% of women. Bacterial infection was significantly observed in vaginal discharge of women of older age group (p=0.005), rural residence (p<0.01) and pregnant women (p=0.03). The main risk factors for bacterial vaginosis were use of non-hygienic products (p=0.03), long marriage duration (p<0.001). Conclusion: The study concluded that bacteria were the commonest cause of vaginal discharge with and without fungal mixed infection.